2016
DOI: 10.17509/invotec.v11i2.2149
|View full text |Cite
|
Sign up to set email alerts
|

A Challenge of Vocational Education for Preparing Green Employment

Abstract: Currently the vocational education has been oriented to the educational processes in which focusing on the development of the student in order to ready to work professionally and ready to improve their self-potential in particular field work. Meanwhile, today and future jobs in various business sectors and industry are still growing and developing towards green jobs. If there is no counter and solution for this growth of green jobs, then it would create a new gap between the output’s competencies of vocational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This evolution does not diminish the teacher's role but redefines it as that of a facilitator and a repository of knowledge. The institutionalization of the Curriculum 2013 stands as a cornerstone, providing a foundational framework for the educational sector (Asmuni, 2013;Asnawi & Djatmiko, 2016;Hafifah et al, 2022;Minhas & Perret, 2017;Neville & Goetz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This evolution does not diminish the teacher's role but redefines it as that of a facilitator and a repository of knowledge. The institutionalization of the Curriculum 2013 stands as a cornerstone, providing a foundational framework for the educational sector (Asmuni, 2013;Asnawi & Djatmiko, 2016;Hafifah et al, 2022;Minhas & Perret, 2017;Neville & Goetz, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All elements of green skills should be instilled in vocational students, including attitudes, knowledge, and values to create students who are considerate to the environment and skilled people in all aspects of life (Kamis, Hussain, Kob, Yunus, & Rahim, 2018). However, the 2013 curriculum, as currently applied by vocational high schools in Indonesia, has not explained, discussed, implemented, or integrated the green skills concept (Asnawi & Djatmiko, 2015) Setiawan (2017) confirmed that green skills have not been clearly integrated into the Indonesian vocational education curriculum. In addition, vocational teachers do not understand well the term green skills, only its relationship with environmental issues (Handayani, Ali, Wahyudin, & Mukhidin, 2020b); still, they agree that students need to possess green skills, which can be developed through learning.…”
Section: Introductionmentioning
confidence: 99%
“…Work field targeted by graduates is specific. Thus, the vocational school is special education that equips graduates to be competent to work professionally, develop careers in particular areas of expertise (Asnawi & Djatmiko, 2015). In this regard, the Indonesian government has divided SMK into nine fields of expertise which are technology and engineering, energy and mining, information communication technology, health-social work, agribusinessagrotechnology maritime affairs, business and management, tourism, arts and creative industries.…”
Section: Introductionmentioning
confidence: 99%